Model financial intelligence berbasis financial english dan pendidikan karakter untuk meningkatkan literasi dan perilaku keuangan digital gen-z di kabupaten Tolitoli - Ismail Yunus H; Andhy Saputra; Haidar Hasan (Piramida Akademi, 2026)
The rapid expansion of the digital economy has transformed the way Generation Z accesses and utilizes financial services. While digital financial platforms have become increasingly accessible, the ability of young people to critically understand financial information and make sound financial decisions remains limited. This study aimed to develop a Financial Intelligence Model integrating Financial English and Character Education to enhance the financial literacy and digital financial behavior of Generation Z in Tolitoli Regency, Indonesia. The study employed a Research and Development (R&D) approach using the Plomp model, which consists of preliminary investigation, design, construction, evaluation, and revision phases. Data were collected from 120 Generation Z respondents selected through purposive sampling. The findings revealed that financial literacy, Financial English proficiency, character values, and financial intelligence were predominantly at a moderate level. The developed model achieved a validity score of 89.4%, indicating a highly feasible educational framework. A limited field trial demonstrated improvements in financial literacy scores from 64.25 to 80.18 and positive changes across all indicators of digital financial behavior. The study concludes that integrating Financial English and character education within a Financial Intelligence framework provides an effective strategy for strengthening financial competence and promoting responsible digital financial behavior among Generation Z in the era of digital economic transformation.